Hak dan Kewajiban Negara dalam Mengatasi Kejahatan Lintas Batas di Era Digital: Pendekatan Analisis Normatif - Laksito, Joni; Idris, Maulana Fahmi; Waryanto, Agus (Hakim: Jurnal Ilmu Hukum dan Sosial, 2024)
The digital era has significantly increased the complexity of cross-border crimes, particularly cybercrime, which poses substantial challenges for countries, including Indonesia. With a reported rise in cross-border cybercrime incidents of over 50% in the last five years, Indonesia faces critical legal and technical hurdles in combating such threats. This study explores the rights and obligations of states in addressing cross-border cybercrime, focusing on comparing Indonesia's legal framework with international standards, specifically the Budapest Convention. Employing a normative analytical method, this research examines international and national legal documents to identify gaps and evaluate the alignment of Indonesia's cybercrime regulations with global standards. Key findings reveal that Indonesia's cybercrime policies lack mandatory international cooperation mechanisms and are limited to national jurisdiction, which restricts the country’s ability to effectively address cybercrimes involving foreign perpetrators. In contrast, the Budapest Convention emphasizes structured international collaboration, robust privacy protections, and flexible jurisdictional arrangements, providing a comprehensive framework for managing transnational cyber threats. The study concludes that harmonizing Indonesia’s regulations with international standards, such as the Budapest Convention, is essential for improving the nation's capacity to combat cross-border cybercrime. Recommendations include enhancing legal frameworks to mandate international cooperation, establishing specialized units within law enforcement agencies equipped with advanced digital forensic tools, and strengthening privacy protections to align with global norms. This research contributes to the discourse on international cybercrime management by offering practical strategies to bridge regulatory gaps and bolster Indonesia’s position in global cybersecurity collaborations. The findings underscore the urgency for policy reform to address the evolving challenges of digital threats in an interconnected world.